UPAYA GURU DALAM MENINGKATKAN RELIGIUSITAS PESERTA DIDIK (Penelitian di RA Miftahussalam Kecamatan Cijeungjing Kabupaten Ciamis) - Daryaman Daryaman (Tarbiyat al-Aulad: Jurnal Pendidikan Islam Anak Usia Dini, 2020)
Indonesia is a country that is very famous for its eastern culture, and one of them from that eastern culture is that it has very high religious beliefs (religiosity). The nature of religiosity for students is very important and must be owned by all students. Therefore, various efforts continue to be made by the teacher so that students have a high religious nature. The teacher's efforts at RA Miftahussalam Handapherang Cijeiungjing Ciamis so that students have a high religiosity are by making good habits every morning. There are several habits that are developed every morning at RA Miftahussalam, including: 1) the waving method; 2) pray at the beginning of each lesson; 3) say Asmaul Husna; 4) memorize short letters; 5) Islamic stories; 6) Hadith lessons.